2017
DOI: 10.1093/pcp/pcx049
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Involvement in Arabidopsis thaliana Stomatal Opening

Abstract: Stomata within the plant epidermis regulate CO2 uptake for photosynthesis and water loss through transpiration. Stomatal opening in Arabidopsis thaliana is determined by various factors, including blue light as a signal and multiple phytohormones. Plasma membrane transporters, including H+-ATPase, K+ channels and anion channels in guard cells, mediate these processes, and the activities and expression levels of these components determine stomatal aperture. However, the regulatory mechanisms involved in these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…While low concentrations of exogenously applied BRs do not affect stomatal movements, higher BR concentrations can operate in two opposite ways. They either induce stomatal closure [ 105 , 106 ] or, conversely, facilitate the opening of the stomata whose closure was induced by ABA [ 107 ] or impaired by BR deficiency [ 108 ]. It is thus possible that the observed differences in the endogenous BR levels in the leaves of our two maize genotypes could perhaps be somehow connected to the behaviour of their stomata.…”
Section: Discussionmentioning
confidence: 99%
“…While low concentrations of exogenously applied BRs do not affect stomatal movements, higher BR concentrations can operate in two opposite ways. They either induce stomatal closure [ 105 , 106 ] or, conversely, facilitate the opening of the stomata whose closure was induced by ABA [ 107 ] or impaired by BR deficiency [ 108 ]. It is thus possible that the observed differences in the endogenous BR levels in the leaves of our two maize genotypes could perhaps be somehow connected to the behaviour of their stomata.…”
Section: Discussionmentioning
confidence: 99%
“…These implicate that the functional orientation of BR in stomatal movement might be influenced by BR contents. In addition, Inoue et al (2017) showed that BRdeficient mutants (dwf5 and det2-1) has impaired blue lightinduced stomatal opening. Notably, the compromised stomatal opening of the dwf5 mutant was recovered by long-term application of BL (3 weeks) but not by short-term application of BL (4 h).…”
Section: Stomatal Movement Coordinated By Br and Abamentioning
confidence: 99%
“…There is also evidence for a role for brassinosteriods in regulating glucosinolate profiles, which function in defence response against insects in A. thaliana 192 . The det2-1 mutant in A. thaliana has impaired stomatal opening in response to blue light, suggesting a further possible role for brassinosteroids in stomatal opening 193 . One of the apparent orthologues of OG43828/FRAEX38873_v2_000227880 in P. trichocarpa, Potri.T122200 ( Supplementary Fig.…”
Section: Og43828 (Fraex38873_v2_000227880)mentioning
confidence: 99%